Factors related to susceptibility to sport-related injury - Oiness, Kacey, author; Suinn, Richard, advisor; Rickard, Kathryn, advisor; Butki, Brian, committee member; Davalos, Deana, committee member (Colorado State University. Libraries, 2012)
The study examined the role various factors play in an athlete's susceptibility to injury in sport. The study involved 244 participants from various sports and included athletes who participated at the high school level, the collegiate level, and the professional level. Participants completed questionnaires measuring number and severity of injuries, resiliency, competition anxiety, trait anger, social support, coping skills, and overtraining. Results showed that an athlete's history of injury (i.e. number of injuries) is significantly correlated with an athlete's severity of injuries. Additionally, various significant correlations were found between the factors examined and one's number of injuries and/or severity of injuries. The correlations found were between resiliency and number of injuries, anger and severity of injuries, coping skills and severity of injury, number of hours practiced and number of injuries, and rigorousness of practices and number of injuries. Additionally, the study examined possible interactions among the variables studied and found that social support serves as a moderator when looking at the relationship between total hours practiced and number of injuries. Results were also examined for males and females, contact and non-contact sports, and high school, collegiate, and profession athletes separately. While some differences emerged, overall there was not much variation between the various groups. Overall, the current study revealed that there are a number of physical, environmental, and psychological factors that impact an athlete's susceptibility to injury.
Keywords: anger; anxiety; coping; injury; resiliency; sport